Effect of Chitosan on Histology of Reproductive Organs of Female Wistar Rats (Rattus norvegicus) Exposed to Acetate Lead - Purwitasari, Alief Ayu; Rozifa, Annisa' Wigati; Irawan, Dwi Dianita; Kalsum, Umi; Ratnawati, Retty; Nurdiana, Nurdiana; Anita, Kenty Wantri (Fakultas Kedokteran Universitas Brawijaya, 2019)
Lead is one of the pollutants widely spread in the environment because it is not easily decomposed. Lead can affect system functions such as the ovary and endometrium. Lead can trigger oxidative stress by reducing antioxidant enzymes and increasing Reactive Oxygen Species (ROS). Lead can also reduce Follicle Stimulating Hormone (FSH) and Luteinizing Hormone (LH) levels by disturbing the hypothalamus. Chitosan is an antioxidant compound that can reduce the toxic effects of lead. The purpose of this study was to study the effects of chitosan administration on the diameter of antral follicles, the number of endometrial arterioles, and the thickness of endometrial rats after lead acetate exposure. This study was an experimental laboratory using a posttest-only control group design approach applied on 25 female rats aged 8 weeks old, body weight 125-175 grams. Lead and chitosan were given orally with a sonde. There were 5 groups, namely, negative control group (without any treatment), positive control group (lead 175mg/kg/BW), treatment group 1 (lead 175mg/kg/BW + chitosan 16mg/kg/BW, treatment group 2 (lead 175mg/kg/BW + chitosan 32mg/kg/BW), and treatment group 3 (lead 175mg/kg/BW + chitosan 64mg/kg/BW) for 30 days. The rats were sacrificed at proestrus phase, which was proven from vaginal swab. Observations were carried out using the Hematoxylin Eosin (HE) staining method. The observations were analyzed using One Way ANOVA and followed by Least Significant Differences (LSD) test. The results showed significant results (p-value <0.05). Chitosan can increase the diameter of the antral follicle, increase the number of endometrial arterioles, and increase the thickness of endometrial rats exposed by lead acetate.